The Role of Educators as 'Among' in Education in the Era of Revolution 4.0 - Roberto Reno Sitepu (Journal of Social Research, 2022)
Background: Education is part of human rights for all human beings. Nowadays education is dealing with various social phenomena such as "flood of information" and "hoaxes" so students experience confusion in going through the educational process. Inspired by Ki Hadjar Dewantara's educational concept, educators can utilize Information and Communication Technology to provide facilities, coordination, and support for students. Objective: This study describes the condition of education, especially in the field of technology during the Revolutionary era. Methods: Researchers used a qualitative approach with descriptive research. Results: The need for increased information on students by utilizing technology, especially information technology. Conclusion: Increasing information will become a dynamic in the academic environment, especially in the lives of students.